Complex Analysis of Business Environment in the Czech Republic in 2006-2022 - Kušnírová, Jana; Zubíková, Adéla; Kozák, Jan, 1990-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
The thesis evaluates the development of the quality of the Czech business environment in the period from 2006 to 2022. A combination of five selected indicators is used for the construction of the composite measure of the quality of the business environment. Based on the development of the individual indicators and the composite measure, the thesis offers a summary of the weaknesses of the Czech business environment. It is accompanied by various policy recommendations for the affected areas. The theoretical part of the thesis is dedicated to the typology of businesses based on various criteria and lists the factors that affect the business environment, according to the up-to-date research. Competition, one of the key parts of the business environment, and five selected indicators, their subcategories, and methods are examined in detail. The time series and comparative analysis of the selected indexes and the composite measure build on the literature research. According to the conducted analysis, the business environment reached its highest quality in 2018 and 2022, respectively. The quality of the business environment has been assessed to be strongly negatively correlated with the unemployment rate and weakly positively correlated with the annual GDP growth. The quality of the business environment in the Czech Republic experienced an increasing trend over the examined period.
Vedoucí práce: Adéla Zubíková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses